1988
DOI: 10.1002/j.1930-2398.1988.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumors of the Major Salivary Glands in Children

Abstract: During the 30-year period 1955-1985, 21 children with neoplasms of the major salivary glands were treated at the Johns Hopkins Hospital. A thorough review of the English literature revealed an additional 472 cases. The cases were studied as to age, sex, site, histopathologic characteristics, mode of treatment, and results. The majority of the patients were between 8 and 20 years of age. There was a female preponderance of 1.42:1. The parotid gland was the site of origin in 85.1%, the submandibular in 11.7%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
7

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 28 publications
7
55
1
7
Order By: Relevance
“…From the Johns Hopkins series [4] , age at time of diagnosis ranged from 1 to 20 years old, with an average of 14.7 years. Average time from detection of mass to seeking medical attention was 21 months.…”
Section: Pleomorphic Adenomamentioning
confidence: 99%
“…From the Johns Hopkins series [4] , age at time of diagnosis ranged from 1 to 20 years old, with an average of 14.7 years. Average time from detection of mass to seeking medical attention was 21 months.…”
Section: Pleomorphic Adenomamentioning
confidence: 99%
“…The enucleation or local excision for parotid gland tumor had been previously performed in children; however, the recurrent rates were very high [2]. Recently the superficial parotidectomy or the total parotidectomy has been a standard operation for parotid gland tumors, resulting in that the recurrence significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, salivary neoplasms account for less than 10% of all pediatric head and neck tumors [1]. A large collective study including 472 pediatric cases of salivary gland neoplasms has demonstrated that the ratio of malignancy in salivary gland tumors in children was higher (49%), which was much higher than that in adults (15-25%) [2]. The benign neoplasms of parotid glands in children are mostly pleomorphic adenoma [3,4]; however, few pediatric case with Warthin tumor has been reported in English literature [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most common malignant salivary gland tumor in children is mucoepidermoid carcinoma, which occurs mainly in older children and young people, but is also a problem in children under 10 [6]. Other malignant salivary gland tumors are adenoid cystic carcinoma, non-differentiated carcinoma, cancer originating from alveolar cells and sarcoma [7]. The paper presents two examples of the difficulties encountered in the diagnosis of parotid salivary gland tumors in children.…”
Section: Introductionmentioning
confidence: 99%